المسائل الصرفية المتعلقة بالأسماء في تحفة الأحوذي دراسة تحليلية دلالية ............................... The Morphological Debates in Tuhfat al-Ahwadhi: A Commentary on Sunan al-Tirmidhi by Abd al-Rahman al-Mubarakpuri, an Indian Muslim Scholar (d. 1353 AH) - اختر, رقية (الدراسات الإسلامية, 2019)
This research paper assesses the linguistic efforts of ‘Abd al-Rahman Mubarakpuri (d. 1353 AH) along with his contribution to this field and impacts of his work on his successors. Mubarakpuri is considered one of the most significant Indian scholars particularly in the study of the traditions of the holy Prophet (peace be upon him). He played an important role in the development of Arabic linguistics in Indian subcontinent. He achieved fame due to his commentary on a famous hadith collection known as Sunan al-Tirmidhi. Therefore, I explored semantical and morphological aspects of his commentary on Sunan al-Tirmidhi. Likewise, I have attempted to explore how he applied his syntactic knowledge to the traditions of the holy Prophet (peace be upon him). Moreover, I have collected all problems related to my topic in order, so that the researchers may gain benefit from them. In this research work, I have elaborated the ideas of this great Muslim scholar. He is one of the earliest Indian grammarians of Arabic. Keywords: linguistics, morphology, Hadith commentary, Mubarakpuri, Tuhfat al-Ahwadhi.